The Influence of Halide Substituents on the Structural and Magnetic Properties of Fe6Dy3 Rings - Kühne, Irina A.; Anson, Christopher E.; Powell, Annie K. (Frontiers in Chemistry, 2020)
We report the synthesis and magnetic properties of three new nine-membered Fe(III)-Dy(III) cyclic coordination clusters (CCCs), with a core motif of [Fe6Dy3(m-OMe)9(vanox)6(X-benz)6] where the benzoate ligands are substituted in the para-position with X = F (1), Cl (2), Br (3). Single crystal X-ray diffraction structure analyses show that for the smaller fluorine or chlorine substituents the resulting structures exhibit an isostructural Fe6Dy3 core, whilst the 4-bromobenzoate ligand leads to structural distortions which affect the dynamic magnetic behavior. The magnetic susceptibility and magnetization of 1 - 3 were investigated and show similar behavior in the dc (direct current) magnetic data. Additional ac (alternating current) magnetic measurements show that all compounds exhibit frequency-dependent and temperature dependent signals in the in-phase and out-of phase component of the susceptibility and can therefore be described as field-induced SMMs. The fluoro-substituted benzoate cluster 1 shows a magnetic behavior closely similar to that of the corresponding unsubstituted Fe6Dy3 cluster, with Ueff = 21.3 K within the Orbach process. By increasing the size of the substituent towards 4-chlorobenzoate within 2, an increase of the energy barrier to Ueff = 36.1 K was observed. While the energy barrier becomes higher from 1 to 2, highlighting that the introduction of different substituents on the benzoate ligand in the para-position has an impact on the magnetic properties, cluster 3 shows a significantly different SMM behavior where Ueff is reduced in the Orbach regime to only 4.9 K.